2013
DOI: 10.1063/1.4813602
|View full text |Cite
|
Sign up to set email alerts
|

Pump-beam-induced optical damage depended on repetition frequency and pulse width in 4-dimethylamino-N ′-methyl-4-stilbazolium tosylate crystal

Abstract: We investigated the dependence of optical damage to an organic nonlinear optical crystal of 4-dimethylamino-N′-methyl-4′-stilbazolium tosylate (DAST) on the repetition frequency and pulse width of the pump beam used to cause the thermal damage. For a pump beam with a pulse width of 15 ns at a wavelength of 1064 nm, the highest damage threshold of 8.0 J/cm2 was measured for repetition frequencies in the range from 10 to 40 Hz. On the other hand, DAST crystals were easily damaged under the repetition rates from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
5
1
Order By: Relevance
“…The experiment revealed that the optical damage threshold for 3.3 μm pumping was twice as high as that for 800 nm pumping, as depicted at the bottom of Figure 2. In the case of DAST, this behavior was reasonable while using the 3.3 μm DC-OPA because the repetition rate of less than 50 Hz and ultra-short pulses result in a high damage threshold owing to the reduced thermal effect [19]. Further, saturation of the THz-wave output was not observed in this experiment and no optical damage occurred on both the NLCs.…”
mentioning
confidence: 55%
See 2 more Smart Citations
“…The experiment revealed that the optical damage threshold for 3.3 μm pumping was twice as high as that for 800 nm pumping, as depicted at the bottom of Figure 2. In the case of DAST, this behavior was reasonable while using the 3.3 μm DC-OPA because the repetition rate of less than 50 Hz and ultra-short pulses result in a high damage threshold owing to the reduced thermal effect [19]. Further, saturation of the THz-wave output was not observed in this experiment and no optical damage occurred on both the NLCs.…”
mentioning
confidence: 55%
“…Further, since the longer wavelength light has lower photon energy, it is expected to reduce the rise in temperature of the NLC when the light becomes the dominant absorption band. The DC-OPA laser has a low repetition frequency; therefore, it provides sufficient time for the NLCs to cool down [19]. In contrast, phase-matching condition in the MIR region is not as satisfying as in the NIR region.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In ref. 19 , Matsukawa et al show that beyond 40 Hz (using ns and ps pulses) the damage threshold of DAST deceases with repetition rate. Although this effect is not yet reported in the fs regime, it is practically conceived.…”
Section: Resultsmentioning
confidence: 99%
“…Zhou et al studied the damage thresholds of K9 glass and UBK7 glass optical components at different pulse widths, then analyzed the pulse-width dependence of damage threshold [13]. Matsukawa et al studied the pump-beam-induced optical damage depending on the pulse width in 4-dimethylamino-N -methyl-4 -stilbazolium tosylate crystal [14]. At present, the damage theory of optical thin films with different pulse widths has been formed.…”
Section: Introductionmentioning
confidence: 99%